EL-MUKARANETÜ BEYNE MENHECI DUATI'T-TECDID VE'L-MÜTEMESSIKIN BI MENHECI'S-SELEF LI TEFSIRI'L-KUR'ANI'L-KERIM (MUHAMMED ABDUH VE EŞ-ŞINGITÎ NEMUZECEN) - SHEKHO, MOHAMMED SADIQ ABDULAZEEZ (Fırat Üniveristesi, 2017)
Bu araştırma tefsirde iki metodun mukayesini hedeflemektedir. Bir metod vardır ki, tefsirde nakle dayanmaktadır. Kur'an'ı anlamada aklıda ihmal etmemektedir. Diğer bir metod ise tefsirde aklı kullanmakta ve nakle çok az yer vermektedir. Akli yöntemi kullanmaya gayret edenler Kur'an'ı asrın yeni gelişmelerine ayak uydurarak tefsir etmeye çalışmaktadırlar. Böylece selefin metoduna muhalefet etmektedirler. Naklî tefsir metodunu kullananlar ise yeni ortaya çıkan konuların hükümlerini de açıklamayı ihmal etmeden selefin metoduna uygun olarak Kur'an'ı tefsir etmeye önem vermektedirler. Bu konudaki yeni tefsir şartlarını inkar etmeden bunu yapmaktadırlar. Bu araştırma aklî metodu kullanan Muhammed Abduh ile tefsirde naklî metodu kullanan eş-Şinkıtî'nin tefsir yöntemlerini mukayeseden ibarettir. Bu mukayese tefsir ilmindeki bazı aklî ve fıkhî meselerdeki bu iki âlimin metodunun karşılaştırılmasından ibarettir.

The purpose of this research is to compare two approaches in interpretation, One of the approaches is based on the transferring and archaeology in interpretation, as well as undiminishing the importance of the mind to understand the Quran, and the other one is based on the mind as well as diminishing the importance transferring and archaeology. The owners of the mental approach tried to explain the Quran in a new interpretation In accordance with the developments of the era, they disagreed with the Salaf approach, while the owners of the archaeological approach interested in interpreting the Quran according to the Salaf approach, while not neglecting to explain the provisions of the developments through the interpretation of the Quran, While not denying the renewal of the interpretation provided that the conditions and controls are regarded for that. The research includes a comparison between the approach of Mohammed Abdoh, the owners of the mental approach and the approach of Al-Shanqeeti one of the most prominent owners of the archaeological approach in interpretation, and this comparison is in the approach of these two Sheikhs in some issues of the science of interpretation, And the interpretation of some of the doctrinal issues. And some jurisprudential issues.
Kur'an-ı kerim tefsirinde tecdid âlimlerinin metodu ile selef metodunu benimseyen âlimlerin metodunun mukayesesi (Muhammed Abduh ve eş-Şingitî örneği)
Keywords: Din